Unveiling the Forgotten Rasaushadha: A Critical Review of ‘Vadavanala Ras’ as Mentioned in Rasa Yoga Sagara (International Journal of Ayurveda and Pharma Research, 2025)
Vadavanala Ras is an herbomineral preparation mentioned in various Ayurveda classical books. Vadavanala Ras, a mysterious and elusive Ayurvedic formulation, has long been shrouded in obscurity. Despite its potential therapeutic benefits, this ancient remedy has been largely overlooked in modern times, with no available commercial preparations or comprehensive literature reviews. This article aims to resurrect the knowledge of Vadavanala Ras, delving into its historical context, pharmacological properties, and potential clinical applications. Rasayoga Sagara of – century has mentioned 26 distinct formulations of Vadvanala Ras that is presently unavailable in market. This pioneering study seeks to revive interest in this forgotten gem, encouraging further research and development of Vadavanala Ras as a valuable addition to the Ayurvedic pharmacopeia.